Hearing impairment in systemic sclerosis patients—what do we really know? - Sieśkiewicz, Michał; Rębacz, Damian; Sieśkiewicz, Andrzej (Frontiers in Medicine, 2024)
Background: Systemic sclerosis is a disease of a very heterogeneous clinical picture and immunological profile with progression rate that varies between individuals. Although hearing deterioration is not a complaint that comes to the fore in SSc patients, as it is not life-threatening compared to many other more severe symptoms of this disease, it can significantly impair the quality of life. Medical literature concerning this problem is rather scarce. Materials and Methods: In this article we systematically reviewed the medical publications concerning hearing impairment in patients with systemic sclerosis to evaluate current understanding of this complex problem. Following PRISMA guidelines a total of 19 papers were found and analysed including 11 original studies and 8 case reports. Results: Although it seems that hearing impairment in SSc patients is relatively more common than in the general population, based on the analysis of available literature, no firm conclusions regarding its frequency and pathomechanism can be drawn yet. Microangiopathy leading to damage to the sensory cells of the inner ear is suspected to be the main mechanism of hearing loss, although damage to the higher levels of the auditory pathway appears to be underestimated due to incomplete audiological diagnosis. Conclusions: Undoubtedly, the reason for the difficulty in such an evaluation are the complex and still not fully elucidated pathomechanism of SSc, the individually variable dynamics of the disease and the unique heterogeneity of symptoms. Nevertheless, further studies in larger and appropriately selected groups of patients, focused more on the dynamics of microangiopathy and not solely on clinical symptoms could provide answers to many key questions in this regard.